Collaborative Strategies of Islamic Religious Education Teachers and Parents in Strengthening Students’ Islamic Moral Character in the Digital Era - Salahuddin Al Ayyubi; Mahariah Mahariah (STAI Serdang Lubuk Pakam, 2026)
This study analyzes the collaboration between Islamic Religious Education teachers and parents in developing students’ morality at SMA Muhammadiyah 18 Sunggal. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving the principal, homeroom teachers, Islamic Religious Education teachers, and parents. Data were analyzed using the Miles, Huberman, and Saldaña interactive model through data condensation, data display, and conclusion drawing, with source and technique triangulation used to ensure data credibility. The findings indicate that collaboration is implemented through student activity reporting books, WhatsApp groups, home visits, parenting guidance, and parent–teacher meetings during report-card distribution. These mechanisms facilitate communication, monitoring, evaluation, and reinforcement of Islamic values between school and family environments. However, collaboration faces challenges related to parents’ limited time, digital communication barriers, and differences in perceptions regarding educational responsibilities. The study concludes that strengthening flexible communication, clarifying responsibilities, and developing sustainable parenting programs are essential for establishing an integrated school–family partnership in students’ moral development.